Adapting to the digital age: Strategies for enhancing customer engagement and retention in e-commerce - Rahmat Hidayat; Yolanda Masnita Siagian; Kurniawati Kurniawati (Journal of Innovation in Business and Economics, 2024)
This research investigates the correlation between customer e-retention (ERT) and various motivational factors of customer engagement, including website design (WD), reliability (RL), and perceived ease of use (PEU). Furthermore, this research was designed to test several mediating factors, including customer e-trust (OT) and customer e-satisfaction (EST), towards customer e-retention (ERT). This research applied a method of purposive sampling to 256 respondents. AMOS employs the Structural Equation Model (SEM) for data processing. This research found that ERT is influenced by reliability (RL), perceived ease of use (PEU), and customer e-trust (OT). Furthermore, two factors do not affect customer e-retention: website design (WD) and customer e-satisfaction (EST). In response to these findings, it is recommended that more attention be paid to building customer engagement and motivation to retain customers online. This may include the quality of information on the website, visual quality, and ease of use.